Parental role in ARI prevention with ARI recurrence in toddlers in Deli Serdang - Nurhaida, Nurhaida; Widyawati, Widyawati; Astuti, Tani; Sihotang, Havija; Apriani, Riny; Gustina, Jessi (Institute of Computer Science (IOCS), 2024)
ARI is a substantial cause of morbidity and mortality in children especially under 5 years of age worldwide. Each year more than 12 million ARIs are registered in hospitals. Recurrence is considered if respiratory tract infection with ≥ 3 episodes or respiratory tract disease or more than 15 days of symptoms in the last 3 months. Objective to determine the relationship of parental role in ARI prevention with ARI recurrence in toddlers in Deli Serdang Regency. The research design used was descriptive correlation research using a cross sectional study approach. The samples taken in this study were parents who had children under five (aged 12-59 months) who had suffered from ARI in Deli Serdang Regency who met the inclusion criteria, with a total of 208 respondents. The results of the study found that the role of parents in the prevention of ARI in Deli Serdang Regency is mostly good as much as 81.7%, the recurrence of ARI in toddlers is more experiencing no recurrence, namely 66.8%. The conclusion of this study is that there is a relationship between the role of parents and the recurrence of ARI in toddlers in Deli Serdang Regency with a p value of 0.00.